The effectiveness of an interactive courseware using three different strategies / Teoh Sian Hoon ... [et al.] - Teoh, Sian Hoon; Toh, Seong Chong; Ngah, Nor Azilah; Kor, Liew Kee (2009)
This paper examines the cognitive effects, in terms of the gain scores and time-on-task of a computer courseware using collaborative and mastery learning strategies. A total of 262 Form Four students from four Malaysian schools interacted with two Matrices courseware: one with mastery learning elements (used in CML and CCML strategies) and another without mastery learning elements (used in CCL strategy). This study showed that, CCML and CML were the effective learning tools. If the time allocated for the learning process is longer, CCML would be the most ideal strategy otherwise CML is generally preferred in the learning process.